A novel coagulation assay incorporating adherent endothelial cells in thromboelastometry - Zipperle, Johannes; Schlimp, Christoph J.; Holnthoner, Wolfgang; Husa, Anna-Maria; Nürnberger, Sylvia; Redl, Heinz; Schöchl, Herbert (Thrombosis and Haemostasis, 2013)
Following vascular injury or activation, endothelial cells (ECs) participate in the modulation of haemostasis and fibrinolysis. Viscoelastic tests (VETs) are a potent bedside monitoring tool that reports haemostatic parameters in real time. However, VETs neglect the influence of the surrounding endothelium. Our aim was therefore to establish an assay that incorporates ECs in a whole blood VET and to assess the impact of ECs on coagulation parameters. Outgrowth endothelial cells (OECs) and human umbilical vein endothelial cells (HUVECs) were seeded onto microbeads to create transferable EC-microcarriers. Microbeads were then added to citrated whole blood in the measurement cup of a thromboelastometry device (ROTEM). After the addition of CaCl2 (star-TEM®) to the blood sample (NATEM assay), standard ROTEM parameters were analysed. Scanning electron microscopy (SEM) was carried out to visualise the interactions of the beads, whole blood components and the ROTEM pin after clotting. SEM showed that the added microbeads were effectively incorporated into the final blood clot. In the presence of activated ECs, the clotting time (CT) of the blood was shortened fourfold compared to that in uncoated control beads. A significant reduction in CT was also observed in the presence of unstimulated ECs. Interestingly, CT was also reduced by the addition of purified EC culture supernatant. CT shortening was prevented by incubating the supernatant with an inhibiting antibody against tissue factor (TF). Our findings demonstrate that ECs can be incorporated into a ROTEM assay via coated microbeads, and whole blood clotting initiation is accelerated by non-activated and activated ECs.
Keywords: Endothelial cells; viscoelastic tests; thromboelastometry; tissue factor